بعض القياسات الجسمية لذراع الرامية وعلاقتها بمهارة دقة التصويب من الثبات لدى لاعبي كرة اليد فئة الناشئين - الله, أ. م. د. هانا جلال فتح (Sulaimani Journal for Humanities, 2024)
This research aims to identify some physical measurements of the length of the throwing arm and the skill of accurate recording of stability among handball junior players, and to identify the type of relationship between some physical measurements of the arm of the thrower and the skill of accurate recording. . The researcher used the descriptive approach, and the sample was selected from handball players at the Koya Sports Club for the year 2022-2023, and their number was (18) players, and some physical measurements related to the players. The thrower's arm length, overall length, forearm length, humerus length, and hand width were chosen. The research sample consisted of 15 players, who were deliberately selected, and the variables were measured, after which the data was collected, unpacked and processed using the (V19) software system (SPSS) lt The researcher reached the following conclusions, that there is a high direct positive relationship between the length and the performance of the skill of accurate shooting in terms of stability, that is, the greater the length of the player, the greater the accuracy of stability, and that there is a high direct positive relationship between the length of the shooting arm and its parts with the performance of the skill of accurate shooting in terms of stability, that is, The greater the arm length, the greater the accuracy, and showed that there was no significant correlation between the length and width of the hand and the performance of the skill of accurate shooting from the stability of the research sample. Especially the total length of the body, and the length of the arm.
Keywords: Physical measurements; pitchers arm length accuracy; stability; scoring; handball